Education 3640. Problems and issues in special education. No. 23. Physically handicapped II. A visit to the Hub. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Wayne Nesbit introduces a film entitled "Issues in Education, Helping People Help Themselves - The Hub", produced by Linda Pfeiffer and Dr. Wayne Nesbit, hosted by Linda Pfeifer and Cathy Boak. The film is a site visit to The Hub, a service centre for the physically handicapped in St. John's. "L. Karagianis, W. Nesbit";"An ETV Colour Production."